Use of information and communication technologies in teaching and learning - Alzhanov Айтуган; Dzhumagalieva Самал (Рroblems of engineering and professional education, 2023)
This article briefly reviews the ICT in the educational process. It also covers the IT devices, which have become essential educational tools and training issues, training of teachers in ICT use.